PENGEMBANGAN MODUL PEMBELAJARAN KIMIA MATERI STRUKTUR ATOM BERBASIS AL-QURAN DI SMAN 1 ACEH BARAT DAYA - Teuku Badlisyah; Wahyu Munawwarah (UIN AR-RANIRY, 2017)
Chemistry subject is one of difficult subject considered by high school students. The difficulty of studying chemistry was related to the characteristics of chemistry it self Chemistry is abstract. So, in the learning process teachers should use a good and an optimal learning resources. One of learning resources that can be used is learning module. In developing learning modules, teacher can relate the subject with the science of religion. So that, besides getting knowledge about chemistry, the students can also increase the insight of religion Islam. Because of the position of education growing the value of religion, occupies a very important place. The arm of this research was to know the design of module and the eligibility of learning chemistry module based Al-qur'an and student learning result by using chemistry learning module based on Al-qur'an at SMAN 1 Aceh Barat Daya. The populations of this study were students at of X MIA in SMAN 1 Aceh Barat Daya which consist of 5 classes i.e. 150 students. While, the samples of this study were students of X MIA-3 which were consist of 24 students. This study was Research and Development (R&D). According to Borg & Gall development research was a process which used to develop and validate educational products. The techniques of Data collection was used validation sheet techniques, trials, questionnaires and giving multiple-choice test. The validation, trial, test and questionnaire result were analyzed by using percentage technique. The results showed that the percentage of validation results refers to very interesting / worthy to use that was equivalent to 85.45% and in the trial module got percentage of 93,33% and percentage of student responses included into interested criterion that was 87,91% for answer